The Effect of Investment, Poor Resident, and International Tourists on Gross Regional Domestic Product In North Sumatera in 2001-2020 - Anggi Kartika; Trisna Saputri; Reynalda Utari Karo-Karo; Romagiano Machario Sembiring; Muammar Rinaldi (Outline Publisher, 2024)
This study aims to determine the effect of the investment sector, poor people, and foreign tourists on economic growth in North Sumatra. This research uses descriptive quantitative research methods. The data used in this study are secondary data and time series data for 2001-2020. The results in this study indicate that investment has a positive and significant effect on GRDP in North Sumatra, the poor have a negative and significant effect on GRDP in North Sumatra, foreign tourists have a positive and significant effect on GRDP in North Sumatra.